Pengolahan Data Keuangan Menggunakan MYOB Premier V16 Pada Bengkel Berkah - Artika Surniandari; Suherman Suherman (LPPM Universitas Bina Sarana Informatika, 2021)
Bengkel Berkah Motor is a company engaged in the automotive trade and services sector that sells motorbike spare parts and repair services, Bengkel Berkah still applies a traditional manual system and has not been computerized in its business process. So it is very possible for data manipulation and errors in recording and calculating sales and purchase transactions of goods. For this reason, the Blessing Workshop requires a computerized system to assist in recording transactions and financial reports. Manual financial data processing systems require a relatively long time and require skill and accuracy in presenting financial statements. On this occasion, the authors made an example of the process of accounting records at the Motor Blessing Workshop which was previously done manually by the author, proposed to be done computerized using Myob Premier V16. Myob Premier is a computerized accounting application that provides convenience in the business administration process by integrating general ledger, finance, purchasing, sales, inventory and relationship processing functions starting from document input to financial reports, using Myob Premier is one of the best solutions for solve existing problems and with a computerized system can produce accurate financial reports, effective and efficient, making it easier for owners